Forest Fires Mapping and Monitoring of current and past forest fire activity from Meteosat Second Generation Data - Carvalheiro, Luis Carlos (2010)
An operational visualization tool for forest fire events monitoring (named forest fires online/offline mapping and monitoring application, and shorthanded as FOMA) is presented. It can be used in two different modes: the near real-time mode, for the online display of actual possible and probable fires, or in retrospective mode, allowing the visualization of past forest fire occurrences. The application is based on the data obtained by the European Organization for the Exploitation of Meteorological Satellites (EUMETSAT) Active Fire Monitoring (FIR) product, obtained from the Meteosat Second Generation (MSG) –2 satellite. The results of this tool, running in the online mode, are automatically uploaded to a web page, providing information about active and potential fires in near-real time. For further investigations, the retrospective mode allows access to processed information, in the Keyhole Markup Language (KML) format, regarding the history of occurrences of forest fires. The EUMETCast reception system is described, and the scientific basis of the FIR product is referenced. The operational implementation of the visualization tool is presented, and some results are shown, considering forest fire occurrences in Portugal, confirmed by the Portuguese Forestry Service.